2012
DOI: 10.1002/nau.21232
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with OAB experience bladder sensations in the same way as healthy volunteers? A focus group investigation

Abstract: Patients with OAB describe their bladder sensations as a pressure or a tingling sensation. There appear to be two types of urgency: a sudden absolute need to void and a slowly developing absolute need to void. Furthermore bladder sensation develops significantly different in volunteers than in OAB patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 17 publications
6
37
1
Order By: Relevance
“…A limitation of this study was that the sample comprised only English‐speaking Australians and thus care should be taken when extrapolating the results of this study cross culturally or internationally in jurisdictions where English is not spoken or where different variations of the English language are used. Nevertheless, the language categories developed in this study are consistent with previous reports of both recalled and induced urge/urgency sensations from countries including the United Kingdom, United States of America, and the Netherlands (Dutch language translated into English) . Recently published studies have provided some detail on the derivation of descriptors, such as use of focus groups, or interviews, whereas earlier studies appear to have derived descriptors from authors' clinical experience, or from previously published summaries of sensation .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A limitation of this study was that the sample comprised only English‐speaking Australians and thus care should be taken when extrapolating the results of this study cross culturally or internationally in jurisdictions where English is not spoken or where different variations of the English language are used. Nevertheless, the language categories developed in this study are consistent with previous reports of both recalled and induced urge/urgency sensations from countries including the United Kingdom, United States of America, and the Netherlands (Dutch language translated into English) . Recently published studies have provided some detail on the derivation of descriptors, such as use of focus groups, or interviews, whereas earlier studies appear to have derived descriptors from authors' clinical experience, or from previously published summaries of sensation .…”
Section: Discussionsupporting
confidence: 83%
“…In contrast to previous studies, the current study provides evidence that differences exist in the language used by individuals with and without OAB. Heeringa et al reported that patients with OAB volunteered similar descriptors of sensation as healthy participants. However, their focus group methodology was an iterative process, where participants shared ideas to consensus.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although many of the biomechanical properties require both urodynamic (pressure) and ultrasound (geometric) data, volume and perimeter strain only require geometric data and had the best correlation to sensation. These parameters can be measured by taking serial ultrasound measurements throughout filling induced by non-invasive oral hydration (De Wachter et al, 2014; Heeringa et al, 2012; Heeringa et al, 2012; Nagle et al, 2016). Measuring perimeter strain only requires the luminal area to be traced, which could potentially be accomplished automatically using edge detection; therefore, this parameter has high potential to be developed as a stand-alone noninvasive test or screening tool used before urodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the invasiveness, patient risk, and cost of this test, non‐invasive hydration protocols have been developed to characterize real‐time bladder sensation in patients with and without OAB . Some of these studies have used a tablet‐based sensation meter that participants used to track real‐time, unprompted bladder sensation .…”
Section: Introductionmentioning
confidence: 99%